2020
DOI: 10.1111/1467-8268.12446
|View full text |Cite
|
Sign up to set email alerts
|

Does financial development reduce the size of the informal economy in sub‐Saharan African countries?

Abstract: This paper contributes to the understanding of the other neglected effects of financial development by investigating the relationship between financial development and the size of the informal economy using an unbalanced panel data of 41 Sub Saharan African countries over the period 1991-2015. Empirical evidence is based on Ordinary Least Squared, Fixed effects and system Generalized Method of moment. The results show that financial development measured by broad money and domestic credit to private sector have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…Also, Bayar & Ozturk, (2016) have found a negative effect of financial development on the shadow economy in the long term by using panel data in European Union transition economies during the period of 2003 to 2014. In the same line, Njangang et al (2018) have found that financial development causes to reduction in the shadow economy's volume in forty-one of the Sub Saharan African states from 1991 to 2015.…”
Section: The Links Between Shadow Economy and Financial Developmentmentioning
confidence: 86%
See 1 more Smart Citation
“…Also, Bayar & Ozturk, (2016) have found a negative effect of financial development on the shadow economy in the long term by using panel data in European Union transition economies during the period of 2003 to 2014. In the same line, Njangang et al (2018) have found that financial development causes to reduction in the shadow economy's volume in forty-one of the Sub Saharan African states from 1991 to 2015.…”
Section: The Links Between Shadow Economy and Financial Developmentmentioning
confidence: 86%
“…The study uses the most used indicators as a proxy for financial development in previous literature. Main indicators that are used in this study are; (1) Private credit by deposit money banks (Private Credit) to account for the ability to access financial resources introduced by banks (Berdiev & Saunoris, 2016;Gharleghi & Jahanshahi, 2020), (2) Bank concentration (BankConcentration) as a proxy to the efficiency of the financial system (Affandi & Malik, 2019;Ardizzi et al 2014;Bose et al 2012), and (3) domestic credit to private sector (DomesticCredit) as a proxy to availability and diversity of the financial system (Bayar & Ozturk, 2016;Bose et al, 2012;Njangang et al, 2018). To be able to link the shadow economy (Shadoweconomy) and economic growth (GDPGROWTH), the study used the GDP growth rate as a proxy of economic growth (GDPGROWTH).…”
Section: Methodsmentioning
confidence: 99%
“…However, the remittances sent by the expatriates are used in five main categories being repayment of loans, the purchase of land, food and clothing, home construction and savings (International Organisation for Migration, 2014). Njangang, Noubissi & Nkengfack (2018) found a positive impact of remittance on the local economy of the recipient countries because it increases the size of their local economy. This finding is also supported from the study of Adams & Page (2005).…”
Section: Literature Reviewmentioning
confidence: 98%
“…The study by Liu‐Evans and Mitra (2019) finds that financial development and informal employment are negatively related. Finally, taking 41 sub‐Saharan countries as a case study and using an unbalanced panel data set over the period 1991–2015, and applying different econometric techniques, Njangang et al (2020) investigate the impact of financial development on the informal economy. They document a nonlinear relationship (U‐shaped) between financial development and the informal economy, suggesting that the informal economy first decreases until a certain threshold of financial development is reached and increases thereafter.…”
Section: Informal Economy Financial Development and Remittances: Thmentioning
confidence: 99%